The problem of a prenoetic dimension of being in The Enneads by Plotinus - Woszczyk, Agnieszka (Folia Philosophica, 2008)
The article is devoted to the issue of the constitution of kosmos noetos - the sphere of being out of the prenoetic. Plotinus distinguishes the elements logically earlier than the being itself which also differ from being principles such as hen and aoristos dyas. Thus, there is a difficulty with defining an ontic status of these indirect elements which are not a being yet however differ from the Unity as such and indefiniteness per se. It concerns mainly the status of numbers and primary diversity and movement. The very difficulty derives from a connection of a dynamic perspective of reality in the categories of self-evoking power with the ontology of being understood as Unity-Multitude.